2006
DOI: 10.1111/j.1469-0691.2006.01385.x
|View full text |Cite
|
Sign up to set email alerts
|

Serological evidence of Rickettsia infections in forestry rangers in north-eastern Italy

Abstract: The prevalence of antibodies to Rickettsiae and other tick-borne microrganisms in the sera of 181 forestry rangers from Friuli-Venezia-Giulia, Italy, was examined. Seven (3.9%) sera were positive for Rickettsia conorii and Rickettsia helvetica, as single or dual infections; four of these sera had been found previously to be positive for Borrelia burgdorferi. Antibodies to Coxiella burnetii were detected in five (2.8%) sera, four of which were also positive for B. burgdorferi. These findings indicate that patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 11 publications
1
17
0
1
Order By: Relevance
“…Few data are reported in Italy on the seroprevalence of C. burnetii in humans [15][16][17][18] air filter systems in housing and movement controls) are effective in reducing infection risk [19].…”
Section: Discussionmentioning
confidence: 99%
“…Few data are reported in Italy on the seroprevalence of C. burnetii in humans [15][16][17][18] air filter systems in housing and movement controls) are effective in reducing infection risk [19].…”
Section: Discussionmentioning
confidence: 99%
“…R. helvetica was first isolated from I. ricinus in Switzerland in 1979(Beati et al, 1993 and has later been identified in I. ricinus collected in Switzerland, Italy, France, Germany, Sweden, Denmark, Bulgaria, and Portugal (reviewed by Parola et al, 2013). The first fatal case, in which R. helvetica was implicated, was reported in Sweden in 1999 (Nilsson et al, 1999), and later human cases have been demonstrated also in other European countries (Cinco et al, 2006;Fournier et al, 2000;Nilsson et al, 2010). The distribution of R. helvetica is not limited to Europe but extends to Japan and the Far-East of Russia, where this pathogen has been detected also in I. ovatus and in I. persulcatus (Fournier et al, 2002;Inokuma et al, 2007;Movila et al, 2011;Nefedova et al, 2008;Shpynov et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…There is a large body of literature that documents the increased risk of acquiring tick-borne diseases among outdoor workers, primarily among forestry workers, farmers, and park rangers (Munchhoff et al 1987, Smith et al 1988, Baird et al 1989, Guy et al 1989, Nadal et al 1989, Goldstein et alet al 2001, Covert and Langley 2002, Piacentino and Schwartz 2002, Niscigorska et al 2003, Santino et al 2004, Zwolinski et al 2004, Tomao et al 2005, Adamek et al 2006, Cinco et al 2006, Dybowska et al 2007, Kaya et al 2008. The methods of tick bite prevention recommended by the National Institute for Occupational Safety and Health (NIOSH 2008) for outdoor workers include the following: wearing light-colored protective clothing, tucking pants into socks or boots, regular application of insect repellant to exposed skin, spraying work clothing with permethrin, and daily tick checks.…”
Section: Introductionmentioning
confidence: 99%